A nanoconjugate Apaf-1 inhibitor protects mesothelial cells from cytokine-induced injury. - Beatriz Santamaría (Public Library of Science (PLoS), 2009)
Background Inflammation may lead to tissue injury. We have studied the modulation of inflammatory milieu-induced tissue injury, as exemplified by the mesothelium. Peritoneal dialysis is complicated by peritonitis episodes that cause loss of mesothelium. Proinflammatory cytokines are increased in the peritoneal cavity during peritonitis episodes. However there is scarce information on the modulation of cell death by combinations of cytokines and on the therapeutic targets to prevent desmesothelization. Methodology Human mesothelial cells were cultured from effluents of stable peritoneal dialysis patients and from omentum of non-dialysis patients. Mesothelial cell death was studied in mice with S. aureus peritonitis and in mice injected with tumor necrosis factor alpha and interferon gamma. Tumor necrosis factor alpha and interferon gamma alone do not induce apoptosis in cultured mesothelial cells. By contrast, the cytokine combination increased the rate of apoptosis 2 to 3-fold over control. Cell death was associated with the activation of caspases and a pancaspase inhibitor prevented apoptosis. Specific caspase-8 and caspase-3 inhibitors were similarly effective. Co-incubation with both cytokines also impaired mesothelial wound healing in an in vitro model. However, inhibition of caspases did not improve wound healing and even impaired the long-term recovery from injury. By contrast, a polymeric nanoconjugate Apaf-1 inhibitor protected from apoptosis and allowed wound healing and long-term recovery. The Apaf-1 inhibitor also protected mesothelial cells from inflammation-induced injury in vivo in mice. Conclusion Cooperation between tumor necrosis factor alpha and interferon gamma contributes to mesothelial injury and impairs the regenerative capacity of the monolayer. Caspase inhibition attenuates mesothelial cell apoptosis but does not facilitate regeneration. A drug targeting Apaf-1 allows protection from apoptosis as well as regeneration in the course of inflammation-induced tissue injury.